The effect of self-efficacy and work discipline on Indonesian police officers's performance: The mediating role of work environment: Pengaruh efikasi diri dan disiplin kerja terhadap kinerja aparat kepolisian: Peran mediasi lingkungan kerja - Nur Aulia; Harianto Respati; Boge Triatmanto (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2024)
This study analyzes the effect of self-efficacy and work discipline on police officers' performance, with the work environment as a mediating variable. Ordinary least square (OLS) is used to examine both direct and indirect relationships among variables. The study was conducted at the Resort Police in Sidoarjo. The results show that self-efficacy and work discipline significantly affect the work environment and performance. Furthermore, the work environment partially mediates the relationship between self-efficacy and work discipline on performance, indicating that a supportive environment strengthens the impact of individual factors on performance. These findings imply that enhancing self-efficacy and discipline alone is not sufficient. Efforts to create a positive work environment are equally important. It is recommended that police institutions provide regular training to build self-efficacy, enforce clear discipline policies, and improve the quality of the work environment to optimize overall performance.